Protection Geographical Indication of Cimpa Tuang Food: Measuring Cultural and Economic Value in Sukalaju Village - Dedek Harianto; Ade Tamaria Sitanggang; Nadila Septiani Ritonga; Rosaria Sianipar; Parlaungan Gabriel Siahaan; Reh Bungana Beru Perangin Angin (Edumaspul: Jurnal Pendidikan, 2023)
Geographical Indication (GI) for cimpa food in the context of measuring the value of cultural and economic identity of a particular region. Cimpa food, as a culinary product with deep cultural roots, has a central role in a region's cultural identity, reflecting local history, traditions and culinary richness. However, challenges such as social, economic, and environmental changes have threatened the sustainability of cimpa food production and the integrity of its cultural identity. This research involved field research methods, surveys, historical analysis, and interviews with producers, local stakeholders. We focused our attention on one specific geographical area where cimpa food is produced. In addition, we measured the economic impact of cimpa food production and marketing, assessed the effectiveness of GI protection, and identified challenges and opportunities faced by producers. Our findings reveal that GI protection is an important measure to protect cimpa food from counterfeiting and unfair competition, while appropriate marketing strategies can expand the market for these products. This research not only provides practical benefits for local producers in developing their businesses, but also makes a theoretical contribution to the understanding of the relationship between food, culture, economics, and legal protection in the context of food products with specific geographical origins.